Law and opinion in twentieth-century Britain and Ireland - Morgan, W. John (ed.); Livingstone, Stephen (ed.) (New York, 2003)
This book takes as its starting point Albert Ven Dicey's classic account of Law and Public Opinion in England in the 19th Century, followed in mid-century by a collection Law and Opinion in 20th Century England , edited by Professor Morris Ginsberg. The present volume takes up a number of themes identified in these earlier volumes, but also considers fresh issues that demonstrate the relationship between law and opinion in Britain. The essays it contains focus on main themes: The Citizen and the State, Public Morality and the Citizen, Culture and Identity and The Death of the English Constitution? Each is analyzed through two detailed and complementary essays authored by leading academics from an appropriate discipline. The book provides a substantial and readable analysis of the relationship between law and opinion in britain and Ireland, with a special focus on the questions of citizenship, culture, identity and the state. As Sir Colin Campbell says in his Preface, the book is 'rich and suggestive' and identifies 'many of the fundamental and subversive issues which will have to be addressed in coming years.'
Keywords: Law